The Free State of Bavaria - between Christianization and secularism - Springer, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with issues related to the phenomena of secularization and secularism in the Free State of Bavaria. The analysis includes changes in attitudes towards religion in recent years, the perception of church institutions and the transformation of religiousness, and the partial disappearance of religiousness and the effects of multiculturalism in the context of the attachment to tradition and the strong cultivation of the Bavarian cultural identity.
Keywords: secularization; secularism; religion; faith; individualization of religion; institutional church; cultural identity